Direct visualization of endogenous Salmonella‐specific B cells reveals a marked delay in clonal expansion and germinal center development. Issue 2 (20th November 2014) - Nanton, Minelva R.; Lee, Seung‐Joo; Atif, Shaikh M.; Nuccio, Sean‐Paul; Taylor, Justin J.; Bäumler, Andreas J.; Way, Sing Sing; McSorley, Stephen J.
<x xml:space="preserve">Abstract</x> CD4+ T cells and B cells are both essential for acquired immunity to Salmonella infection. It is well established that Salmonella inhibit host CD4+ T‐cell responses, but a corresponding inhibitory effect on B cells is less well defined. Here, we utilize an Ag tetramer and pull‐down enrichment strategy to directly visualize OVA‐specific B cells in mice, as they respond to infection with Salmonella‐OVA. Surprisingly, OVA‐specific B‐cell expansion and germinal center formation was not detected until bacteria were cleared from the host. Furthermore, Salmonella infection also actively inhibited both B‐ and T‐cell responses to the same coinjected Ag but this did not require the presence of iNOS. The Salmonella Pathogenicity Island 2 (SPI2) locus has been shown to be responsible for inhibition of Salmonella‐specific CD4+ T‐cell responses, and an examination of SPI2‐deficient bacteria demonstrated a recovery in B‐cell expansion in infected mice. Together, these data suggest that Salmonella can simultaneously inhibit host B‐ and T‐cell responses using SPI2‐dependent mechanisms.